Graphene-polyelectrolyte multilayer membranes with tunable structure and internal charge. (30th April 2020) - Liu, Yang; Zheng, Sunxiang; Gu, Ping; Ng, Andrew J.; Wang, Monong; Wei, Yangyang; Urban, Jeffrey J.; Mi, Baoxia
Abstract: One great advantage of graphene-polyelectrolyte multilayer (GPM) membranes is their tunable structure and internal charge for improved separation performance. In this study, we synthesized GO-dominant GPM membrane with internal negatively-charged domains, polyethyleneimine (PEI)-dominant GPM membrane with internal positively-charged domains and charge-balanced dense/loose GPM membranes by simply adjusting the ionic strength and pH of the GO and PEI solutions used in layer-by-layer membrane synthesis. A combined system of quartz crystal microbalance with dissipation (QCM-D) and ellipsometry was used to analyze the mass deposition, film thickness, and layer density of the GPM membranes. The performance of the GPM membranes were compared in terms of both permeability and selectivity to determine the optimal membrane structure and synthesis strategy. One effective strategy to improve the GPM membrane permeability-selectivity tradeoff is to assemble charge-balanced dense membranes under weak electrostatic interactions. This balanced membrane exhibits the highest MgCl2 selectivity (∼86%). Another effective strategy for improved cation removal is to create PEI-dominant membranes that provide internal positively-charged barrier to enhance cation selectivity without sacrificing water permeability. These findings shine lights on the development of a systematic approach to push the boundary of permeability-selectivity tradeoff for GPM membranes. Graphical abstract: Image 1